EVALUATION OF OAT VARIETIES UNDER SUFFICIENT AND INSUFFICIENT IRRIGATION - Nadhum Y. Abed; Hussein Kzar Shalal Al-essawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the genetic variations of Oat cultivars under in sufficient of irrigation. A field experiment was carried out at the fields of with College of Agricultural Engineering Sciences ;University of Baghdad - Al-Jadriya during 2020-2021 seasons. The experiment was carried out using a Completely Block designwithin split-plot arrangement using three replicates under two treatments (verities and irrigation intervals). The main plots were irrigation intervals with moisture(50%, 25%, and 10%), while sub-plots were the varieties (Genzania, Anatolia, Plmula, Algoda, and Al-Shifa).The results showed that the third irrigation level had 75% flowering at highest averages93.67 days , and the V4 variety had the lowest average to weight of 250 grains about (7.67 g ).While there was a significant differencesamong irrigation interval 75% flowering compared with other traits ( 22.8) ,(24.6 )and ( 7.75) respectively. While the Alogoda produced the highest yield (7.49 ton .h-1) compared with the lowest Plmula gave (5.83 ton h-1)There are differences among of varieties under irrigation intervals. The highest genotypic coefficient to yield (94.7%) and the highest value of heritability was (98.75%).to the flowering.